Model pengurusan kualiti bagi perkhidmatan teknologi maklumat: Fokus kepada bahagian perkhidmatan pengguna sektor awam - Othman, Mohd Khalit (Universiti Utara Malaysia, 2006)
This study is about quality management in the computing services department in the public sector focussing on the IT Services Division (BPTM), User Services Division and Computing Services Division (BPP/BPK). The purpose of this study is to discuss and reveal the concept of quality management where the definitions of the quality and quality management have been elaborated. This study also develops a model of quality management for the organisations and investigates whether the elements that are included in the model are able to be fully applied in these departments. In order to fulfil the requirements the study, of 100 sets of questionnaires were distributed to the 50 randomly selected public sector department as respondents to get their opinions and perceptions. From the 100 sets of questionnaires, 86 were collected and used for data analysis using the SPSS package. As a result, this study has revealed the quality management elements and aspects to be looked into. Furthermore, based on the results of the discovery of theories and research data, this study has developed a practical quality management model to be executed in BPTM. A detailed discussion about research methodology, data processing and data analysis has been explained in this study. As a conclusion, this study has revealed the principles and the aspects that are needed to upgrade the quality management, more specifically for BPTM.